Report of the Committee of Experts on the Application of Conventions and Recommendations : General Report and observations concerning particular countries. - Office, International Labour (International Labour Conference 101st Session 2012, Report III1A., 2012)
The Committee of Experts on the Application of Conventions and Recommendations, whose work constitutes the cornerstone of the ILO's supervisory system on international labour standards, has just published its annual report.